Tax consequences of insolvency (bankruptcy) of entities: problems and decisions - Казачкова, Земфира; Казачков, Владимир (Studia Iuridica Toruniensia, 2018)
The purpose of this article is to reflect the essence of tax consequences in the field of insolvency and bankruptcy. Until recently the bankruptcy was identified by dishonest taxpayers as a way to avoid the relevant payments. Nevertheless, the novels of legislation and institutional reforms changed the situation. The recent issue describes the main aspects of taxing in the field of different principles and procedures of bankruptcy. The key directions of administration of added value tax, profit taxes, and tax of private income are analyzed in this article.